Farmland Use Efficiency among Muktakamaiya Households in Gauriganga Municipality, Kailali - Pathak, Dipendra; Upadhyay, Santosh; Pandit, Samikshya; Dhakal, Bishnu (Journal of the Institute of Agriculture and Animal Science, 2025)
The Muktakamaiya, an indigenous Tharu group of former bonded workers liberated in 2000 A.D., were given only small landholdings (2-5 kattha) by the Nepalese government. However, household with similar landholdings have uneven income levels. Some households are able to secure livelihood from farm production, whereas some others are able to secure it. This study aimed to assess the farmland use efficiency of the Muktakamaiya households in Gauriganga Municipality, Kailali District. A total of 87 households were sampled through simple random sampling and analyzed using SPSS software. The result showed that only 57% of Muktakamaiya farmers were able to generate income from their agricultural land, with an average gross income of NRs. 1625 per unit kattha land, ranging from NRs. 45 to 12487. A binary logistic regression analysis suggested that agricultural-related training support and the number of modern technologies to their farm had significant impacts on farmland use efficiency. Especially, the farmers with agricultural training and technological support used their land three (3) and seven (7) times more efficiently than those without. The findings underscored the use of proper technologies and addressing challenges support enhancing agricultural productivity. Expanding access to agricultural training programs and subsidies for modern agricultural technologies is recommended to enhance farmland use efficiency and ensure sustainable livelihood for the Muktakamiya farmers.